The Impact of Nurses Job Stress Level on Patients Care in Tertiary Care Hospital: Nurses Job Stress Level on Patients Care in Hospital - Yasin, Muhammad Talha; Rafiq, Nasim; Hameed, Alina; Yasir, Muhammad; Ahmed, Rida; Ali, Shehbaz (Pakistan Journal of Health Sciences, 2023)
Nursing is dynamic in nature and nurses are often in high level of job stress because of hard job, work load and burden of responsibilities. These stressors can have negative effect on patient care. The focus of study was to evaluate the correlation of nurses’ job stress and quality of care delivered to patients. Objective: To assess the nurses job stress level and the association of job stress and patient care at tertiary care hospital. Methods: The descriptive cross-sectional study was conducted with 144 participants working in tertiary care hospital. The nurses were selected via convenient sampling technique. The duration of study was 6 months. The data were collected by demographic characteristics, Caring Dimension Inventory (CDI-25) and NIOSH Generic Job Stress Questionnaire. Results: The results of this study showed that numbers of females were more 126 (87.5%) and majority of participants in age limit of 21-30 were 92 (63.9%). Most of the participants were bachelor degree holder 137 (95.1) and official job holders were 127 (88.2) at that institute. Large numbers of participants were bed side nurses 124 (86.1%). Most of the nurses felt moderate level of job stress (76.4%) and provide poor patient care (43.1%). The p-value of 0.001 was indication of the conclusion that there were association between nurses’ job stress and patient care delivered to patient. Conclusions: There was significant relation between the job stress and patient care. The job stress had negative effect on patient care delivered to patient by nurses. It also reduced the nurses’ performance which maybe factor of poor patients’ outcome